KERUSAKAN HUTAN MANGROVE DI DESA DOLAGO KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Narka, Made Sintia Dewi; Korja, I Nengah; Ramlah, Sitti (Jurnal Warta Rimba, 2018)
Mangrove is an ecosystem with uniqe function in the life environment. Because of the influence of sea and land, there was complex interaction happened between physical and biological properties in the mangrove area. The physical properties of mangrove able to act as breakwater as well as an intrusion detterent and sea abrasion.Â  Litter decomposition process of mangrove that occurs can support the life of living things in it. The existence of Mangrove forest that is located in Dolago village of South Parigi sub-district at Parigi Moutong district which alleged to have suffered damage, therefore it is necessary to do research related with the damage of mangrove forest in that village. This study aims to find out the condition of the damage of forest mangrove and the physical-chemical condition of water. This study have been conducted in Dolago village, South Parigi Sub-District, Parigi Moutong District in March until May 2016. The water analysis was conducted in Natural Resources and Environmental Analysis Laboratory of Agriculture Faculty Tadulako University. This study used Line Transect and Trasect Line Plot. Data obtained from 3 paths that have been made. Water sampling conducted on each path of vegetation observation. The result showed that the mangrove forest in Dolago village has been damaged with classified as moderately damage by the density 1233 btg/ha. The influence of physical-chemical of water condition at study site is still relatively good and has not been contaminated to support the growth of mangrove. However, the relative salinity value in a state exceeds of the standards set. Keywords: Damage, Forest, Mangrove